Afrohybanthus indicus (Violaceae): a new species from Maharashtra, India - Kamble, Suhas Kundlik; Forster, Paul I; Patil, Bhimrao Janardan (Phytotaxa, 2016)
A new species Afrohybanthus indicus is described and illustrated. It differs from A. stellarioides and A. enneaspermus in the characters of stipule, leaf margin and pedicel.